Water: The Only Factor Influencing the Price of Energy in the Spot Market? - Vinicius Mothé Maia; Bruno Lessa Meireles; Marcelo Cabús Klötzle; Antonio Carlos Figueiredo Pinto; Leonardo Lima Gomes (Revista Sociedade, Contabilidade e Gestão, 2016)
The Brazilian electric energy generation system is based on its hydroelectric power plants, making the country dependent on proper rainfall and, thus, raising the possibility of energy stress situations, such as the energy-rationing scenario observed in the beginning of the century and the latest water crisis (2014). Moments of water scarcity are followed by an increase in energy prices, which affects the economy as whole. Therefore, it is relevant to understand which factors in the Brazilian Electric System affect the energy price and the individual importance of each. This paper aimed to analyze which the key variables influencing the energy price in the spot market are by using official data from the National Electric System Operator. The used data was from the period July/2001 to July/2014, which was employed in a multiple regression methodology along with time series. The results suggest an inverse relationship between the natural flow of rivers (directly related to rainfall) and the energy price. Moreover, they also point to an inverse relationship between the potential energy stored in reservoirs as water and the energy price.